Resolving the Chemical Formula of Nesquehonite via NMR Crystallography, DFT Computation, and Complementary Neutron Diffraction. Issue 5 (29th December 2022) - Cui, Jinlei; Prisk, Timothy R.; Olmsted, David L.; Su, Vicky; Asta, Mark; Hayes, Sophia E.
Abstract: Nesquehonite is a magnesium carbonate mineral relevant to carbon sequestration envisioned for carbon capture and storage of CO2 . Its chemical formula remains controversial today, assigned as either a hydrated magnesium carbonate [MgCO3 ⋅ 3H2 O], or a hydroxy‐ hydrated‐ magnesium bicarbonate [Mg(HCO3 )OH ⋅ 2H2 O]. The resolution of this controversy is central to understanding this material's thermodynamic, phase, and chemical behavior. In an NMR crystallography study, using rotational‐echo double‐resonance 13 C 1 H (REDOR), 13 C− 1 H distances are determined with precision, and the combination of 13 C static NMR lineshapes and density functional theory (DFT) calculations are used to model different H atomic coordinates. [MgCO3 ⋅ 3H2 O] is found to be accurate, and evidence from neutron powder diffraction bolsters these assignments. Refined H positions can help understand how H‐bonding stabilizes this structure against dehydration to MgCO3 . More broadly, these results illustrate the power of NMR crystallography as a technique for resolving questions where X‐ray diffraction is inconclusive. Abstract : NMR crystallography and neutron diffraction can settle a longstanding debate regarding the chemical formula for the CO2 mineralization target species, nesquehonite, through examination of the effects of H on 13 C tensors. It is a hydrated magnesium carbonate [MgCO3 ⋅ 3H2 O], and not a hydroxy‐ hydrated‐ magnesium bicarbonate.